2010
DOI: 10.1007/s11244-010-9464-1
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics and Mechanisms for Hydrolysis and Transesterification of Triglycerides on Tungstated Zirconia

Abstract: Hydrolysis and transesterification are two reactions which can occur during the synthesis of biodiesel. An Investigation of the mechanistic pathways in hydrolysis and transesterification were carried out at a relatively high temperature (100-130°C) and moderate pressures (120-180 psi) with tricaprylin and water for hydrolysis or methanol for transesterification using a tungstated zirconia catalyst in a batch reactor. It was found that upon increasing the concentration of TCp, the reaction rates for both hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
1
11
0
1
Order By: Relevance
“…As known, acidity of WZ catalyst is a key factor to enhance the catalytic activity for several reactions by generation of active sites [2][3][4][5][6][7][8][9][10][11][12][13]. The catalytic active sites were plausible for high surface acidity form with a monolayer of polytungstated species (WO x ) [3,4,11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As known, acidity of WZ catalyst is a key factor to enhance the catalytic activity for several reactions by generation of active sites [2][3][4][5][6][7][8][9][10][11][12][13]. The catalytic active sites were plausible for high surface acidity form with a monolayer of polytungstated species (WO x ) [3,4,11].…”
Section: Resultsmentioning
confidence: 99%
“…A heterogeneous catalyst as a tungsten oxide supported on zirconia (WZ) has been tremendously used for alkane isomerization [2][3][4][5], alcohol dehydration [6,7] and recently biodiesel forming reaction [8][9][10][11][12][13]. This is because of their acid properties, stability under reducing and oxidizing conditions and regenerability [14].…”
Section: Introductionmentioning
confidence: 99%
“…The three ester groups with large molecular weight are replaced by methanol with small molecular weight to produce the fatty acid methyl ester and glycerol with small molecular weight. [ 31,32 ]…”
Section: Resultsmentioning
confidence: 99%
“…The simulated results also showed that increasing the initial ethanol concentration increases the initial production rate and yield of fatty acid ethyl ester and lowers the final concentration of free fatty acid. Using a tungstated zirconia catalyst, Ngaosuwan et al 107 investigated the mechanistic pathways for hydrolysis (with water) and transesterification (with methanol) of tricaprylin and found that increasing the concentration of tricaprylin increased the reaction rates for both hydrolysis and transesterification under all conditions. However, water inhibited the reaction rate of hydrolysis by poisoning the active sites.…”
Section: Saponification and Hydrolysismentioning
confidence: 99%